2020
DOI: 10.1007/s10661-020-08698-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the metal pollution in surface sediments of coastal Tasaul Lake (Romania)

Abstract: Forty-three surface sediment samples were collected in September 2019 from Tasaul Lake (Black Sea coast, Romania) to examine the metal distribution patterns, assess the level of metal contamination, and identify the pollutant sources. The determined mean metal concentrations were as follows: Al 49,772 mg/kg, Zn 84.40 mg/kg, Cr 83.70 mg/kg, V 76.45 mg/kg, Ni 42.53 mg/kg, Cu 34.27 mg/kg, Pb 26.30 mg/kg, As 12.49 mg/kg, and Hg 0.06 mg/kg. The metals in the surface sediments of Tasaul Lake displayed moderate spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…The validity of PCA was assessed using the Kaiser-Meyer-Olkin test and Bartlett's test. Principal components (PCs) with eigenvalues greater than one were deemed relevant (Vasiliu et al, 2020;Yang et al, 2014). To determine the contribution of elements to a specific group, components with factor loadings > 0.6, 0.4-0.6, and 0.3-0.4 were classified as highly, moderately, or weakly associated with elements in that group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of PCA was assessed using the Kaiser-Meyer-Olkin test and Bartlett's test. Principal components (PCs) with eigenvalues greater than one were deemed relevant (Vasiliu et al, 2020;Yang et al, 2014). To determine the contribution of elements to a specific group, components with factor loadings > 0.6, 0.4-0.6, and 0.3-0.4 were classified as highly, moderately, or weakly associated with elements in that group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Potential toxic metals such as Pb, Cd, Fe, Ni, and Cu with high coefficient values are highly correlated, and this showed that these metals would most likely originate from industrial and domestic discharges that contained these heavy metals [39]. The second component (PCA 2) accounts for about 20% variance and that Si, Al, Cr, Sn variation in the heavy metal concentration in water in location D, Si, Al and Cr are highly correlated and concentrated in that location, which suggests that these metals could originate from natural sources, while the Sn contaminant could be from ship repairing and other anthropogenic sources [57].…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Через насиченість глибинних шарів води сірководнем там існують лише деякі види анаеробних бактерій. Найбільші ріки Чорноморського басейну (Дунай, Дніпр, Південний Буг та Дністр) визначають стан живих біологічних ресурсів усього Чорного моря та вносять ~80% забруднюючих речовин [111,131,132,135].…”
Section: фізико-хімічні показники морської та порової водиunclassified